RUANG BERKUMPUL INFORMAL ANAK DI RUSUNAWA JOGOYUDAN, KAMPUNG GOWONGAN KIDUL KECAMATAN GONDOKUSUMAN YOGYAKARTA - Fiterian Centauri, Ikhwanuddin (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2015)
ABSTRACTThis study is aimed to know the children gathering space, the physical element found in it, andfactors that may affect the establishment of the children gathering space. This study applied aqualitative approach which is to depict or describe a natural condition that occurs. In collectingthe data, the researchers conducted observations in the field to observe the activities ofchildren, physical setting of children gathering space and physical elements in it. The site of thisresearch was conducted at Rusun Jogoyudan Gowongan Kampung Kidul village,Gondokusuman sub-district, Yogyakarta. The findings of this study show that children in thegathering space rusunawa Jogoyudan, Yogyakarta including: stall / guard post, stall / gabion(river banks), the mosque yard (front and side), entrance way. Physical elements childrengathering space at the towers include: a) the floor elements in form of paving blocks floor(mostly), cement pavement and gabion, b) a roof element in form of tritisan stalls and mosquesand, c) the wall elements in form of fences, walls of the house / shop, gabion andembankments. Factors that may affect the establishment of the gathering space are broad view,easily accessible place and shady place, cool air, within near range of children; there are snackstalls and healthy snacks sellers.Keywords: Children gathering space, rusunawa Jogoyudan, settlemen